Metastable multiphase bimodal superfine eutectic high-carbon chromium molybdenum steel

By achieving the in-situ transformation of M7C3/M23C6 during the heat treatment of high-carbon chromium molybdenum steel, the problem of difficult dissolution of large-sized M7C3 carbides is solved, and it generates easy-to-dissolve M23C6 carbides, improving the metallurgical quality and performance of the material.

CN119411021APending Publication Date: 2025-02-11ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411310759.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Large-size M7C3 eutectic carbides in high-carbon chromium molybdenum steel are difficult to dissolve during conventional heat treatment, affecting the processing and use performance of the material.

Method used

By achieving the in-situ transformation of M7C3/M23C6 during the heat treatment of high-carbon chromium molybdenum steel, the converted carbide has a smaller size and easier dissolution properties.

Benefits of technology

Through the in-situ transformation process, small-size, multi-oriented, easily broken and soluble M23C6 carbides are generated, which significantly improves the metallurgical quality and performance of the steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411021A_ABST
    Figure CN119411021A_ABST
Patent Text Reader

Abstract

The invention relates to metastable multiphase double-peak superfine eutectic high-carbon chromium molybdenum steel which is prepared from the following raw materials in percentage by weight: 0.50-1.50% of C; cr: 11.00% to 20.00%; 1.00% to 10.0% of Mo; and the balance of Fe and inevitable impurities. According to the method, the superfine ternary eutectic high-carbon chromium molybdenum steel composed of M23C6 / M6C / Matrix can be obtained; and through the in-situ transformation process, the metastable nanometer ternary eutectic in the solidification structure is further decomposed and refined, stable carbides which are small in size, multi-oriented, easy to crush and soluble are generated, and the metallurgical quality of steel is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high carbon chromium-molybdenum steel manufacturing, in particular to a metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel. Background Art

[0002] High carbon chromium-molybdenum steel is widely used in the field of corrosion-resistant parts such as turbine blades, bearings, valve ports, etc. due to its excellent hardness, elasticity and wear resistance, especially in high-quality knife and shear materials. In order to further improve the performance, the carbon and chromium content in this steel is increased, which promotes the formation of large-sized eutectic M7C3 carbides during solidification. The size of these carbides ranges from a few microns to tens of microns, and their presence can cause chipping, blunting, fracture and even rust on the edge of the tool.

[0003] The production process of high carbon chromium-molybdenum steel includes induction furnace melting, LF refining, casting, consumable electrode preparation, electroslag remelting, hot rolling, spheroidizing annealing, cold rolling, recrystallization annealing, quenching and tempering. Among these steps, the solidification process of electroslag remelting, hot working and heat treatment are the key links to control the eutectic carbides in the steel. By improving the solidification process and adding alloying elements such as Nb, Ti, and rare earth, the size of eutectic carbides can be reduced and their morphology can be improved, but they cannot be completely eliminated. Homogenization and high temperature deformation treatment help to improve element segregation and promote the dissolution or decomposition of large-sized carbides. However, the eutectic M7C3 carbides in high carbon chromium-molybdenum steel remain stable when approaching or exceeding the solidus temperature of the steel, so it is difficult to dissolve during conventional heat treatment and eventually remain in the final product, affecting the processing and use performance of the material.

[0004] In order to eliminate the negative impact of large-sized M7C3 eutectic carbides in high-carbon chromium-molybdenum steel on performance, the present invention focuses on the in-situ conversion of insoluble eutectic M7C3 carbides into M7C3 carbides that are easy to fracture and dissolve at high temperatures. 23 C6 carbide. M7C3 / M 23 C6 in-situ transformation refers to the transformation of homogeneous M7C3 carbides into M7C3 / M6 carbides during heat treatment at an appropriate temperature. 23 The morphology of C6 core-shell structure. The size of M7C3 cemented carbide core gradually decreases with the extension of heat treatment time. The in-situ transformation is conducive to the full crushing of carbides during hot rolling and the complete dissolution of carbides during homogenization.

[0005] At present, the high chromium cast iron and heat-resistant steel M7C3 / M 23 The research on in-situ transformation of C6 mainly focuses on the fields of high chromium cast iron and heat-resistant steel. Pearce studied the M7C3 / M6 transformation of cast iron containing 30% chromium during heat treatment. 23 In situ transformation of C6 revealed that M 23C6 nucleates at the interface between M7C3 and the matrix and grows inward, consuming M7C3. 23 C6 carbides do not inherit the defects of M7C3. Inoue et al. studied the in-situ carbide transformation during tempering of rapidly solidified high carbon Cr-W and Cr-Mo steels and determined that M7C3 carbides and the transformed M 23 The crystallographic relationship between C6 carbides. Vardavoulias et al. found that M7C3 / M 23 The C6 phase transformation creates a continuous carbide network in cast ferritic stainless steels and changes the fracture mechanism from transgranular to interdendritic cleavage.

[0006] At the same time, Kondrat'ev et al. explained the M7C3 / M4 phase transition by increasing the number of metal atoms in the carbon coordination polyhedron from 6 to 8 in the framework of a combined model of metal crystal transformation. 23 The mechanism of in-situ conversion of C6. Wang et al. used computational thermodynamics to describe the M7C3 / M6 transformation in white cast iron. 23 Recently, Wieczerzak et al. determined the in-situ transformation mechanism of M7C3 / M6 in Fe-25Cr0.8C alloy. 23 In-situ transformation of C6 in the temperature range of 500~600℃ revealed that M7C3 / M 23 The first stage of the in-situ transformation of C6 is the upward diffusion of chromium from the matrix to the M7C3 carbides. 23 The C6 core-shell structure means that alloying elements need to pass through M 23 Wang et al. studied the in-situ transformation of HP-MA during heat treatment at 1000℃ and found that chromium in M 23 The diffusion distance in C6 is much smaller than the measured M 23 C6 thickness. Calculation and experimental results show that M7C3 / M 23 The in situ transformation of C6 may be affected by the carbon 23 Diffusion control in C6.

[0007] In order to meet the growing engineering needs, the present invention has developed a method that can achieve M7C3 / M 23 C6 in-situ transformed high carbon chromium-molybdenum steel. Summary of the invention

[0008] The problem to be solved by the present invention is to provide a metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel in view of the above-mentioned deficiencies in the prior art. The in-situ transformation process is applied to the high carbon chromium-molybdenum steel. During the heat treatment process, the homogeneous M7C3 carbide is transformed into M7C3 / M 23C6 core-shell structure, realizing M7C3 / M in high chromium cast iron and heat-resistant steel 23 In-situ transformation of C6 was performed to develop a metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel.

[0009] The above-mentioned object of the present invention is achieved through the following technical solutions: A metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel is made of the following raw materials in weight percentage: C: 0.50~1.50%; Cr: 11.00~20.00%; Mo: 1.00~10.0%; The balance is Fe and inevitable impurities.

[0010] By adopting the above technical solution, carbon (C): carbon is a martensite forming element and is also a metastable eutectic carbide M7C3 / M2C and an in-situ transformed eutectic carbide M 23 C6 / M6C is an important component element. Increasing its content can improve the hardness and wear resistance of steel, but excessive content will increase the brittleness of the material. Therefore, the carbon content in the present invention is controlled between 0.50 and 1.50% to ensure that the material has good comprehensive properties. Chromium (Cr): Chromium is the main element in martensite and is also a key element for improving the corrosion resistance and wear resistance of steel. In the present invention, the chromium content ranges from 11.00 to 20.00% to ensure that the precipitation of metastable carbide M7C3 can be effectively promoted during the heat treatment process while maintaining the corrosion resistance and wear resistance of the material.

[0011] Molybdenum (Mo): Molybdenum is a martensite-forming element. The addition of molybdenum can significantly improve the strength and toughness of steel. Molybdenum can also be beneficial to the precipitation of metastable carbides M2C. In the present invention, the content of molybdenum is 1.00-10.0% to ensure that the expected performance improvement effect is achieved without increasing excessive costs.

[0012] The balance is Fe and unavoidable impurities: Iron is the main component of steel, while unavoidable impurities include elements such as silicon, manganese, phosphorus, and sulfur, which exist in steel at very low levels and have little effect on material properties; Through precise control and optimization of the above components and combined with the following process improvements, the metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel of the present invention can achieve M7C3 / M 23 In situ conversion of C6 can be obtained by M 23Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix; through the in-situ transformation process, the metastable nano-ternary eutectic in the solidification structure is further decomposed and refined to generate small-sized, multi-oriented, easily breakable and soluble stable carbides, which significantly improves the metallurgical quality of the steel.

[0013] Further, it is made of the following raw materials in weight percentage, C: 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40 or 1.50%; Cr: 11.00, 11.10, 11.20, 11.30, 11.40, 11.50, 11.60, 11.70, 11.80, 11.90, 12.00 ,12.10,12.20,12.30,12.40,12.50,12.60,12.70,12.80,12.90,13.00,13.10,13 .20、13.30、13.40、13.50、13.60、13.70、13.80、13.90、14.00、14.10、14.20、14.30、14.40、14.50、14.60、14.70、14.80、14.90、15.00、15.10、15.20、15.30、15.40、15 .50、15.60、15.70、15.80、15.90、16.00、16.10、16.20、16.30、16.40、16.50、16.60、16.70、16.80、16.90、17.00、17.10、17.20、17.30、17.40、17.50、17.60、17.70、1 7.80, 17.90, 18.00, 18.10, 18.20, 18.30, 18.40, 18.50, 18.60, 18.70, 18.80, 18.90, 19.00, 19.10, 19.20, 19.30, 19.40, 19.50, 19.60, 19.70, 19.80, 19.90 or 20.00%; Mo: 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3 .20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, 5.10, 5.20, 5.30, 5.40, 5 .50, 5.60, 5.70, 5.80, 5.90, 6.00, 6.10, 6.20, 6.30, 6.40, 6.50, 6.60, 6.70, 6.80, 6.90, 7.00, 7.10, 7.20, 7.30, 7.40, 7.50, 7.60, 7.70, 7.80, 7.90, 8.00, 8.10, 8.20, 8.30, 8.40, 8.50, 8.60, 8.70, 8.80, 8.90, 9.00, 9.10, 9.20, 9.30, 9.40, 9.50, 9.60, 9.70, 9.80, 9.90 or 10.0%; Furthermore, it is made of the following raw materials in weight percentage, C: 0.90~1.10%; Cr: 14.10~14.60%; Mo: 4.00~4.30%; The balance is Fe and inevitable impurities.

[0014] Further, it is made of the following raw materials in weight percentage, C: 1.00%; Cr: 14.30%; Mo: 4.10%; The balance is Fe and inevitable impurities.

[0015] Furthermore, the preparation process includes preparing raw materials containing C, Cr and Mo according to a ratio, and sequentially subjecting the raw materials to smelting, casting, electroslag remelting, hot rolling and heat treatment to obtain a material composed of M 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix.

[0016] Furthermore, the smelting is specifically implemented as follows: first, raw materials including C, Cr, Mo and pure iron are added to a smelting furnace in sequence, and heated in an argon environment until the raw materials are completely melted, and then the molten pool temperature of the smelting furnace is adjusted to 1520~1600°C, and kept warm for 60~180min. After the smelting is completed, the temperature is lowered until the molten steel temperature is 1450~1600°C, and then molten steel is tapped to obtain molten steel.

[0017] Furthermore, the pouring is specifically implemented by injecting the molten steel obtained by smelting into a mold, controlling the pouring temperature to be 1450-1520°C, and pouring into a cylindrical electrode, wherein the ratio of the diameter of the electrode to the diameter of the crystallizer used for electroslag remelting is 0.7-0.9, and the electrode is obtained after pouring and molding.

[0018] Furthermore, the specific implementation method of the electroslag remelting is to remove the surface oxide layer of the electrode obtained by casting, first place an arc starter and part of the electroslag at the bottom of the crystallizer, pass inert gas argon, and form an arc heating electrode through the electrode and the bottom of the crystallizer. After the arc is successfully struck, the remaining electroslag is gradually added, and the slag layer thickness is controlled to be 25~40% of the diameter of the crystallizer, and the remelting voltage is controlled to be 20~50V, the remelting current range is 3000~6000A, and the inlet temperature of the crystallizer cooling water should be controlled at ≤25℃, and the outlet temperature is 40~60℃; in the shrinkage period when the remelting process is close to the end, the melting speed is gradually reduced by reducing the power, while keeping the voltage constant, slowing down the descending speed of the electrode until the remelting is completely completed; after the remelting is completed, the mold is cooled to room temperature to obtain an electroslag ingot. The steel ingot obtained under the above conditions has the advantages of high purity, fine grains and uniform chemical composition distribution.

[0019] Furthermore, the electroslag is made of the following raw materials in weight percentage: CaF2: 50~90%, CaO: 5~25%, Al2O3: 5~25%.

[0020] Furthermore, the hot rolling is specifically implemented by heating the electroslag steel ingot obtained by electroslag remelting in a heating furnace, heating it in a low temperature zone of 900-1100°C for 60-150 minutes, and heating it in a high temperature zone of 1250-1350°C for 60-120 minutes, then unloading and sequentially undergoing rough rolling and finishing rolling, controlling the steel ingot temperature ≥1050°C during the rolling process, and water cooling it to room temperature after the rolling is completed to obtain a hot-rolled steel ingot. Through the above hot rolling treatment steps, the surface quality of the steel ingot is significantly improved, and the grains are effectively refined, thereby improving the mechanical properties of the material.

[0021] Furthermore, the specific implementation method of the heat treatment is to heat treat the hot-rolled steel ingot obtained by hot rolling, first keep it at 1000-1200°C for 1-7h, then put it into water and quickly cool it to room temperature; then keep it at 150-250°C for 1.5-4h, and finally air cool it to room temperature to obtain M 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix. First, keep it at 1000~1200℃ for 1~7h to transform austenite into martensite, improve the hardness of the material, and transform the large-sized M7C3 into M7C3 / M 23 C6 shell structure, when the heat treatment time is long enough, M7C3 is completely transformed into a small size M 23 C6, and then keep it at 150~250℃ for 1.5~4h, which helps to eliminate the brittleness caused by quenching and improve the toughness of the material.

[0022] Among them, the ternary eutectic structure is a microstructure composed of three chemical components (such as iron, carbon and alloying elements). For high-carbon martensitic stainless steel, the common eutectic phase usually involves the interaction between carbon, chromium and iron. The eutectic structure is generally formed when the liquid metal solidifies, and a microstructure with special physical properties is formed by simultaneous crystallization during the melting process.

[0023] M7C3 / M2C / Matrix is ​​usually composed of three phases: M7C3 carbide, M2C carbide and matrix. In M7C3 carbide, M represents a metal element, mainly chromium, but may also contain other metal elements such as iron. C is a carbon element; in M2C carbide, M is mainly molybdenum (Mo), with a chemical formula of Mo2C. The matrix is ​​the main phase in steel, composed of martensite, which provides support for M7C3 carbide and M2C carbide.

[0024] M 23 C6 / M6C / Matrix is ​​usually composed of M 23 C6 carbide, M6C carbide and matrix are composed of three phases. 23 In C6 carbide, M represents a metal element, mainly chromium, partly molybdenum and iron. The typical chemical formula is Cr 23 In C6;M6C carbides, M is mainly molybdenum (Mo), and the chemical formula is Mo6C. The matrix is ​​the main phase in steel and is composed of martensite.

[0025] The present invention relates to two ternary eutectic structures. Before heat treatment, the ternary eutectic structure in the high carbon chromium-molybdenum steel is M7C3 / M2C / Matrix. During the heat treatment, the large-sized M7C3 undergoes in-situ transformation and transforms into M7C3 / M23 C6 shell structure, when the heat treatment time is long enough, M7C3 is completely transformed into a small size M 23 C6, finally forming ultra-fine M 23 C6 / M6C / Matrix ternary eutectic structure significantly improves alloy quality and product performance.

[0026] In summary, the beneficial technical effects of the present invention are: after adopting the above-mentioned components and process methods, a 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix; through the in-situ transformation process, the metastable nano-ternary eutectic in the solidification structure is further decomposed and refined to generate small-sized, multi-oriented, easily breakable and soluble stable carbides, which significantly improves the metallurgical quality of the steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 1 is a flow chart of the preparation process of Example 1 of the present invention.

[0028] Figure 2 1 is a eutectic carbide structure diagram of the high carbon chromium-molybdenum steel in the cast state according to Example 1 of the present invention.

[0029] Figure 3 It is the morphology, phase distribution and orientation diagram of eutectic carbides of high carbon chromium-molybdenum steel in the cast state of Example 1 of the present invention; wherein, (a)(e)(i)(m)(q) are three-dimensional morphology diagrams, (b)(f)(j)(n)(r) are two-dimensional morphology diagrams, (c)(g)(k)(o)(s) are phase distribution diagrams, (d)(h)(l)(p)(t) are phase orientation diagrams, (u) is a phase distribution diagram legend, and (v) is a phase orientation diagram legend.

[0030] Figure 4 This is the non-equilibrium solidification process of high carbon chromium-molybdenum steel in Example 1 of the present invention; wherein (a) is a phase precipitation sequence diagram, (b) is a diagram of alloy element concentration in the residual liquid, (c) is a diagram of M7C3 carbides, and (d) is a diagram of the Thermo-Calc software simulation results of M2C carbides.

[0031] Figure 5 It is the morphology, phase distribution and orientation diagram of the cast eutectic carbide of the high carbon chromium-molybdenum steel in Example 1 of the present invention after heat treatment at 1000°C for 7 hours; wherein, (a)(d)(g)(j) are morphology diagrams, (b)(e)(h)(k) are phase distribution diagrams, (c)(f)(i)(l) are phase orientation diagrams, (m) is the phase distribution diagram legend, and (n) is the phase orientation diagram legend.

[0032] Figure 6 1 is the XRD diagram of the high carbon chromium-molybdenum steel in Example 1 of the present invention in the cast state and after heat treatment at 1000° C. for 1 h and 7 h. DETAILED DESCRIPTION

[0033] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with the accompanying drawings and specific implementation methods.

[0034] Example 1: A metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel disclosed in the present invention is made of the following raw materials in percentage by weight: C: 1.00%; Cr: 14.50%; Mo: 4.20%; The balance is Fe and inevitable impurities.

[0035] At the same time, refer to Figure 1 The specific implementation method of the preparation process of high carbon chromium-molybdenum steel is as follows: S1 prepares raw materials containing C, Cr and Mo according to a proportion; S2 smelting, first add raw materials including C, Cr, Mo and pure iron into the smelting furnace in sequence, and heat them in an argon environment until the raw materials are completely melted, then adjust the molten pool temperature of the smelting furnace to 1580°C, keep it warm for 120 minutes, and start cooling after smelting until the molten steel temperature reaches 1500°C to tap steel and obtain molten steel; S3 casting, pouring the molten steel obtained by smelting into the mold, controlling the pouring temperature to be 1500°C, and casting into a cylindrical electrode, the ratio of the diameter of the electrode to the diameter of the crystallizer used for electroslag remelting is 0.7, and the electrode is obtained after casting; S4 electroslag remelting, after removing the surface oxide layer of the electrode obtained by casting, first place an arc starter and part of the electroslag at the bottom of the crystallizer, introduce inert gas argon, and form an arc through the electrode and the bottom of the crystallizer to heat the electrode. After the arc is successfully struck, gradually add the remaining electroslag, control the slag layer thickness to 30% of the crystallizer diameter, and control the remelting voltage to 35V, the remelting current range to 4500A, the inlet temperature of the crystallizer cooling water should be controlled at 25℃, and the outlet temperature to 50℃; in the shrinkage period when the remelting process is close to the end, gradually reduce the melting speed by reducing the power, while keeping the voltage constant, slowing down the electrode descent speed until the remelting is completely completed; after the remelting is completed, cool the mold to room temperature to obtain an electroslag ingot; The electroslag is made of the following raw materials in weight percentage: CaF2: 70%, CaO: 15%, Al2O3: 15%; S5 hot rolling, using a heating furnace to heat the electroslag steel ingot obtained by electroslag remelting, heating it in a low temperature zone of 1000°C for 100 minutes and in a high temperature zone of 1300°C for 90 minutes, then unloading and sequentially undergoing rough rolling and finish rolling, controlling the steel ingot temperature at 1050°C during the rolling process, and water cooling it to room temperature after the rolling is completed to obtain a hot-rolled steel ingot; S6 heat treatment, the hot rolled steel ingot is heat treated, first at 1000 ℃ for 7 hours, then put into water and quickly cooled to room temperature; then at 200 ℃ for 2.5 hours, and finally air cooled to room temperature, to obtain M 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix.

[0036] Example 2: A metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel disclosed in the present invention is made of the following raw materials in percentage by weight: C: 0.50%; Cr: 15.00%; Mo: 1.00%; The balance is Fe and inevitable impurities.

[0037] At the same time, refer to Figure 1 The specific implementation method of the preparation process of high carbon chromium-molybdenum steel is as follows: S1 prepares raw materials containing C, Cr and Mo according to a proportion; S2 smelting, first add raw materials including C, Cr, Mo and pure iron into the smelting furnace in sequence, and heat them in an argon environment until the raw materials are completely melted, then adjust the molten pool temperature of the smelting furnace to 1520°C, keep it warm for 60 minutes, and start cooling after smelting until the molten steel temperature reaches 1450°C, and then tap the steel to obtain molten steel; S3 casting, pouring the molten steel obtained by smelting into the mold, controlling the pouring temperature to be 1450°C, and casting into a cylindrical electrode, the diameter of the electrode and the diameter of the crystallizer used for electroslag remelting are 0.75, and the electrode is obtained after casting; S4 electroslag remelting, after removing the surface oxide layer of the electrode obtained by casting, first place an arc starter and part of the electroslag at the bottom of the crystallizer, introduce inert gas argon, and form an arc through the electrode and the bottom of the crystallizer to heat the electrode. After the arc is successfully struck, gradually add the remaining electroslag, and control the slag layer thickness to 25% of the crystallizer diameter. The remelting voltage is controlled to 20V, the remelting current range is 3000A, the inlet temperature of the crystallizer cooling water should be controlled at 20℃, and the outlet temperature is 40℃; in the shrinkage period when the remelting process is close to the end, the melting speed is gradually reduced by reducing the power, while keeping the voltage constant, slowing down the descending speed of the electrode until the remelting is completely completed; after the remelting is completed, the mold is cooled to room temperature to obtain an electroslag ingot; The electroslag is made of the following raw materials in weight percentage: CaF2: 50%, CaO: 25%, Al2O3: 25%; S5 hot rolling, using a heating furnace to heat the electroslag steel ingot obtained by electroslag remelting, heating it in a low temperature zone of 900°C for 60 minutes and in a high temperature zone of 1250°C for 60 minutes, then unloading and sequentially undergoing rough rolling and finish rolling treatments, controlling the steel ingot temperature at 1060°C during the rolling process, and water cooling it to room temperature after the rolling is completed to obtain a hot-rolled steel ingot; S6 heat treatment, the hot rolled steel ingot is heat treated, first at 1050 ℃ for 5 hours, then put into water and quickly cooled to room temperature; then at 150 ℃ for 1.5 hours, and finally air cooled to room temperature to obtain M 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix.

[0038] Example 3: A metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel disclosed in the present invention is made of the following raw materials in percentage by weight: C: 0.90%; Cr: 14.10%; Mo: 4.00%; The balance is Fe and inevitable impurities.

[0039] At the same time, refer to Figure 1 The specific implementation method of the preparation process of high carbon chromium-molybdenum steel is as follows: S1 prepares raw materials containing C, Cr and Mo according to a proportion; S2 smelting, first add raw materials including C, Cr, Mo and pure iron into the smelting furnace in sequence, and heat them in an argon environment until the raw materials are completely melted, then adjust the molten pool temperature of the smelting furnace to 1540°C, keep it warm for 90 minutes, and start cooling after the smelting is completed until the molten steel temperature reaches 1550°C, and then tap the steel to obtain molten steel; S3 casting, pouring the molten steel obtained by smelting into the mold, controlling the pouring temperature to be 1470°C, and casting into a cylindrical electrode, the diameter of the electrode and the diameter of the crystallizer used for electroslag remelting are 0.8, and the electrode is obtained after casting; S4 electroslag remelting, after removing the surface oxide layer of the electrode obtained by casting, first place an arc starter and part of the electroslag at the bottom of the crystallizer, introduce inert gas argon, and form an arc through the electrode and the bottom of the crystallizer to heat the electrode. After the arc is successfully struck, gradually add the remaining electroslag, control the slag layer thickness to 30% of the crystallizer diameter, and control the remelting voltage to 30V, the remelting current range to 4000A, the inlet temperature of the crystallizer cooling water should be controlled at 15°C, and the outlet temperature to 45°C; in the shrinkage period when the remelting process is close to the end, gradually reduce the melting speed by reducing the power, while keeping the voltage constant, slowing down the descending speed of the electrode until the remelting is completely completed; after the remelting is completed, cool the mold to room temperature to obtain an electroslag ingot; The electroslag is made of the following raw materials in weight percentage: CaF2: 60%, CaO: 20%, Al2O3: 20%; S5 hot rolling, using a heating furnace to heat the electroslag steel ingot obtained by electroslag remelting, heating it in a low temperature zone of 950°C for 80 minutes and in a high temperature zone of 1280°C for 80 minutes, then unloading and sequentially undergoing rough rolling and finish rolling, controlling the steel ingot temperature at 1070°C during the rolling process, and water cooling it to room temperature after the rolling is completed to obtain a hot-rolled steel ingot; S6 heat treatment, the hot rolled steel ingot obtained by hot rolling is heat treated, first at 1100 ° C for 4 hours, then put into water and quickly cooled to room temperature; then at 175 ° C for 2.0 hours, and finally air cooled to room temperature to obtain M 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix.

[0040] Example 4: A metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel disclosed in the present invention is made of the following raw materials in percentage by weight: C: 1.10%; Cr: 14.60%; Mo: 4.30%; The balance is Fe and inevitable impurities.

[0041] At the same time, refer to Figure 1 The specific implementation method of the preparation process of high carbon chromium-molybdenum steel is as follows: S1 prepares raw materials containing C, Cr and Mo according to a proportion; S2 smelting, first add raw materials including C, Cr, Mo and pure iron into the smelting furnace in sequence, and heat them in an argon environment until the raw materials are completely melted, then adjust the molten pool temperature of the smelting furnace to 1560°C, keep it warm for 150 minutes, and start cooling after the smelting is completed until the molten steel temperature reaches 1580°C and steel is tapped to obtain molten steel; S3 casting, pouring the molten steel obtained by smelting into the mold, controlling the pouring temperature to be 1490°C, and casting into a cylindrical electrode, the diameter of the electrode and the diameter of the crystallizer used for electroslag remelting are 0.85, and the electrode is obtained after casting; S4 electroslag remelting, after removing the surface oxide layer of the electrode obtained by casting, first place an arc starter and part of the electroslag at the bottom of the crystallizer, pass inert gas argon, and form an arc through the electrode and the bottom of the crystallizer to heat the electrode. After the arc is successfully struck, gradually add the remaining electroslag, control the slag layer thickness to 35% of the crystallizer diameter, and control the remelting voltage to 40V, the remelting current range to 5000A, the inlet temperature of the crystallizer cooling water should be controlled at 10°C, and the outlet temperature to 55°C; in the shrinkage period when the remelting process is close to the end, gradually reduce the melting speed by reducing the power, while keeping the voltage constant, slowing down the electrode descent speed until the remelting is completely completed; after the remelting is completed, cool the mold to room temperature to obtain an electroslag ingot; The electroslag is made of the following raw materials in weight percentage: CaF2: 80%, CaO: 10%, Al2O3: 10%; S5 hot rolling, using a heating furnace to heat the electroslag steel ingot obtained by electroslag remelting, heating it in a low temperature zone of 1050°C for 120 minutes and in a high temperature zone of 1320°C for 100 minutes, then unloading and sequentially undergoing rough rolling and finish rolling treatments, controlling the steel ingot temperature at 1080°C during the rolling process, and water cooling it to room temperature after the rolling is completed to obtain a hot-rolled steel ingot; S6 heat treatment, the hot rolled ingot is heat treated, first at 1150 ° C for 3 hours, then put into water and quickly cooled to room temperature; then at 225 ° C for 3.0 hours, and finally air cooled to room temperature to obtain M 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix.

[0042] Example 5: A metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel disclosed in the present invention is made of the following raw materials in weight percentage: C: 1.50%; Cr: 20.00%; Mo: 10.00%; The balance is Fe and inevitable impurities.

[0043] At the same time, refer to Figure 1 The specific implementation method of the preparation process of high carbon chromium-molybdenum steel is as follows: S1 prepares raw materials containing C, Cr and Mo according to a proportion; S2 smelting, firstly, raw materials including C, Cr, Mo and pure iron are added to the smelting furnace in sequence, and heated in an argon environment until the raw materials are completely melted, and then the molten pool temperature of the smelting furnace is adjusted to 1600°C, and the temperature is kept for 180 minutes. After the smelting is completed, the temperature is lowered until the molten steel temperature reaches 1600°C, and the molten steel is tapped to obtain molten steel; S3 casting, pouring the molten steel obtained by smelting into the mold, controlling the pouring temperature to be 1520°C, and casting into a cylindrical electrode, the diameter of the electrode and the diameter of the crystallizer used for electroslag remelting are 0.9, and the electrode is obtained after casting; S4 electroslag remelting, after removing the surface oxide layer of the electrode obtained by casting, first place an arc starter and part of the electroslag at the bottom of the crystallizer, introduce inert gas argon, and form an arc through the electrode and the bottom of the crystallizer to heat the electrode. After the arc is successfully struck, gradually add the remaining electroslag, control the slag layer thickness to 40% of the crystallizer diameter, and control the remelting voltage to 50V, the remelting current range to 6000A, the inlet temperature of the crystallizer cooling water should be controlled at 5°C, and the outlet temperature to 60°C; in the shrinkage period when the remelting process is close to the end, gradually reduce the melting speed by reducing the power, while keeping the voltage constant, slowing down the descending speed of the electrode until the remelting is completely completed; after the remelting is completed, cool the mold to room temperature to obtain an electroslag ingot; The electroslag is made of the following raw materials in weight percentage: CaF2: 90%, CaO: 5%, Al2O3: 5%; S5 hot rolling, using a heating furnace to heat the electroslag steel ingot obtained by electroslag remelting, heating it in a low temperature zone of 1100°C for 150 minutes and in a high temperature zone of 1350°C for 120 minutes, then unloading and sequentially undergoing rough rolling and finish rolling, controlling the steel ingot temperature at 1100°C during the rolling process, and water cooling it to room temperature after the rolling is completed to obtain a hot-rolled steel ingot; S6 heat treatment, the hot rolled steel ingot is heat treated, first at 1200 ℃ for 1 hour, then put into water and quickly cooled to room temperature; then at 250 ℃ for 4.0 hours, and finally air cooled to room temperature, to obtain M 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix.

[0044] Test Example 1: The high carbon chromium-molybdenum electroslag ingot prepared in Example 1 was used as a test sample. The sample had a diameter of 200 mm, a height of 1100 mm, and a weight of 300 kg. A 35 mm thick thin plate was cut from the lower part of the electroslag ingot, and samples were taken from the center to the edge of the thin plate, the same below.

[0045] Image-ProPlus6.0 software was used to count the average interlamellar spacing and spherulite structure length of different eutectic carbides. The sample for observing the three-dimensional morphology of eutectic carbides was obtained by electrolysis at a voltage of 13V. The electrolyte is an organic solution composed of methanol, tetramethylammonium chloride, glycerol and diethanolamine. For electron backscatter diffraction (EBSD) measurements, the sample was first mechanically polished in a diamond suspension and then electropolished in a perchloric acid alcohol solution for 2 minutes. The EBSD measurement was performed by a JSM-7900F scanning electron microscope, equipped with a symmetrical EBSD detector, operating at 20keV, and the sample was tilted 70°. The test results are shown in the figure. Figure 2 and Figure 3 shown.

[0046] Figure 2 The eutectic carbide is a cast high carbon chromium-molybdenum steel. The overall carbide morphology clearly shows a multimodal distribution of the constituent carbides, and the length scale is not uniform. This non-uniformity is manifested in the coexistence of micron-scale gray eutectic carbides, submicron-scale white eutectic carbides, and nano-scale ultrafine eutectic high carbon chromium-molybdenum steel. Figure 2 (b) and (c) show that the micro-scale gray eutectic carbides have different morphologies, namely blocky, fibrous and spherulitic. There are cavities in the blocky carbides. Figure 2 (d) and (g) show that the ultrafine eutectic high carbon chromium-molybdenum steel is surrounded by white eutectic carbides. The white eutectic carbides show a typical regular lamellar eutectic structure, in which carbides and matrix are arranged alternately, and the average lamellar spacing is 315nm, as shown in Figure 2. Figure 2 As shown in (e) and (h). Figure 2 The ultrafine eutectic carbides in (f) and (i) are actually formed by gray carbides and white carbides. The gray carbides have a spherulite structure with an average length of 191nm. Due to the truncation effect of the gray spherulite carbides in the ultrafine eutectic high carbon chromium-molybdenum steel, the white carbides are separated and refined into a finer lamellar structure with an average lamellar spacing of 217nm and a spherulite structure with an average length of 185nm.

[0047] Figure 3 It shows the morphology, phase distribution and orientation of eutectic carbides before in-situ transformation of as-cast high carbon chromium-molybdenum steel. Figure 3 (a)~(d) show that the micron-sized carbides are M7C3 carbides. Figure 3 (d) It can be seen that Figure 3 The eutectic M7C3 carbide in (b) is composed of multiple carbide grains with different orientations. Our previous work studied the orientation of eutectic M7C3 carbides in cast high carbon chromium-molybdenum steel. The results show that the entire M7C3 carbide cluster between dendrites is composed of multiple M7C3 carbide grains with different orientations; Figure 3(a) to (d) also confirm this phenomenon. Hollowness is often observed in the center of the blocky carbide substructure. Leško et al. first proposed a growth model for the central void of M7C3 carbides based on the dissolution of screw dislocation cores. Due to the inherent screw dislocations, the hexagonal M7C3 carbides form a rotational ladder on the basal plane. The solute atoms in the molten steel preferentially accumulate along the c-axis, so that the residual liquid phase is surrounded by M7C3 carbides, resulting in the formation of a hollow in the center of the large carbide block.

[0048] Depend on Figure 3 From (e) to (l), we can see that the blocky carbides are M7C3 carbides, the submicron-scale layered carbides are M2C carbides, and the adjacent layered carbides have the same orientation. Figure 3 (m)~(t) It can be seen that the ultrafine eutectic high carbon chromium-molybdenum steel is M7C3 carbide and M2C carbide. Adjacent M2C carbide lamellae and spherulites have the same orientation, and adjacent spherulite M7C3 carbides also have the same orientation. In general, the eutectic carbides in the high carbon chromium-molybdenum ESR ingot are the coexistence of coarse binary eutectic M7C3 / matrix, fine binary eutectic M2C / matrix and ultrafine ternary eutectic M7C3 / M2C / matrix.

[0049] Test Example 2: The high carbon chromium-molybdenum electroslag ingot prepared in Example 1 was used as a test sample, and the PE approximation of Thermo-calc software was used to simulate the phase precipitation sequence in the non-equilibrium solidification process. The test results are as follows: Figure 4 shown.

[0050] Depend on Figure 4 (a) It can be seen that when the solid phase fraction increases to 0.79, M7C3 carbides precipitate in the residual liquid phase. When the solid phase fraction reaches 0.96 and the system temperature drops to 1194℃, M2C carbides precipitate. The solidified structure consists of γ~Fe, M7C3 carbides and M2C carbides.

[0051] Figure 4 (b) shows the concentration of residual liquid during nonequilibrium solidification. The results show that the element concentration increases sharply at the end of solidification. When the solid phase fraction reaches 90.3%, the residual liquid phase produces interdendritic eutectic carbides. After the precipitation of interdendritic eutectic carbides, the concentration of carbon continues to increase at a lower rate, and the concentration of carbon and chromium begins to decrease.

[0052] Figure 4 (c) shows the concentration of eutectic M7C3 carbides during nonequilibrium solidification, indicating that M7C3 is a Cr-rich carbide.

[0053] Figure 4 (d) shows the concentration of eutectic M2C carbides during nonequilibrium solidification, indicating that M2C is a Mo-rich carbide.

[0054] Test Example 3: The high carbon chromium-molybdenum electroslag ingot prepared in Example 1 was used as a test sample, and subjected to scanning electron microscopy and XDR testing. The test results are as follows: Figure 5 and Figure 6 shown.

[0055] Figure 5 Morphology, phase distribution and orientation of as-cast eutectic carbides in high carbon chromium-molybdenum steel after heat treatment at 1000℃ for 7h: (a)(d)(g)(j) morphology, (b)(e)(h)(k) corresponding phase distribution, (c)(f)(i)(l) corresponding phase orientation, (m) phase distribution diagram legend, (n) phase orientation diagram legend.

[0056] Figure 6 Figure 2 shows the XRD spectra of high carbon chromium-molybdenum steel before and after heat treatment at 1000℃. The phase composition of cast high carbon chromium-molybdenum steel is γ-Fe, α-Fe, M7C3 and M2C. After heat treatment at 1000℃ for 1h, the phase composition of high carbon chromium-molybdenum steel is α-Fe, M7C3, M2C. 23 C6 and M6C. After heat treatment at 1000℃ for 7h, the phase composition of high carbon chromium-molybdenum steel is α-Fe, M 23 C6 and M6C.

[0057] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel, characterized in that: Made of the following raw materials in percentage by weight: C:0.50~1.50%; Cr:11.00~20.00%; Mo: 1.00~10.0%; The balance is Fe and inevitable impurities.

2. The metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel according to claim 1, characterized in that: Made of the following raw materials in percentage by weight: C:0.90~1.10%; Cr:14.10~14.60%; Mo: 4.00~4.30%; The balance is Fe and inevitable impurities.

3. The metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel according to claim 1, characterized in that: Made of the following raw materials in percentage by weight: C:1.00%; Cr:14.30%; Mo: 4.10%; The balance is Fe and inevitable impurities.

4. A metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel according to any one of claims 1 to 3, characterized in that: The preparation process comprises preparing raw materials containing C, Cr and Mo according to a ratio, and sequentially subjecting the raw materials to smelting, casting, electroslag remelting, hot rolling and heat treatment to obtain a material composed of M 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix.

5. The metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel according to claim 4, characterized in that: The specific implementation method of the smelting is to first add raw materials including C, Cr, Mo and pure iron into a smelting furnace in sequence, and heat them under an argon environment until the raw materials are completely melted, and then adjust the molten pool temperature of the smelting furnace to 1520~1600℃, keep it warm for 60~180min, and start cooling after the smelting is completed until the molten steel temperature is 1450~1600℃ to obtain molten steel.

6. The metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel according to claim 4, characterized in that: The specific implementation method of the casting is to inject the smelted molten steel into the mold, control the casting temperature to 1450-1520°C, and cast it into a cylindrical electrode. The ratio of the electrode diameter to the crystallizer diameter used for electroslag remelting is 0.7-0.9, and the electrode is obtained after casting.

7. The metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel according to claim 4, characterized in that: The specific implementation method of the electroslag remelting is as follows: after removing the surface oxide layer of the electrode obtained by casting, an arc starter and part of the electroslag are placed at the bottom of the crystallizer, an inert gas argon is introduced, and an arc is formed through the electrode and the bottom of the crystallizer to heat the electrode. After the arc is successfully struck, the remaining electroslag is gradually added, and the slag layer thickness is controlled to be 25-40% of the diameter of the crystallizer, and the remelting voltage is controlled to be 20-50V, the remelting current range is 3000-6000A, the inlet temperature of the crystallizer cooling water should be controlled to be ≤25°C, and the outlet temperature is 40-60°C; in the shrinkage period stage when the remelting process is close to the end, the melting speed is gradually reduced by reducing the power, while keeping the voltage constant and slowing down the descending speed of the electrode until the remelting is completely completed; after the remelting is completed, the mold is cooled to room temperature to obtain an electroslag ingot.

8. The metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel according to claim 7, characterized in that: The electroslag is made of the following raw materials in weight percentage: CaF2: 50-90%, CaO: 5-25%, Al2O3: 5-25%.

9. The metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel according to claim 4, characterized in that: The hot rolling is specifically implemented as follows: the electroslag steel ingot obtained by electroslag remelting is heated in a heating furnace, and is heated in a low temperature zone of 900-1100°C for 60-150 min, and in a high temperature zone of 1250-1350°C for 60-120 min, and then the steel ingot is discharged and subjected to rough rolling and finish rolling treatments in sequence. During the rolling process, the temperature of the steel ingot is controlled to be ≥1050°C, and after the rolling is completed, the steel ingot is water-cooled to room temperature to obtain a hot-rolled steel ingot.

10. The metastable multiphase bimodal ultrafine eutectic high carbon chromium-molybdenum steel according to claim 4, characterized in that: The specific implementation method of the heat treatment is to heat treat the hot-rolled steel ingot obtained by hot rolling, first keep it at 1000-1200°C for 1-7h, then put it into water and quickly cool it to room temperature; then keep it at 150-250°C for 1.5-4h, and finally air cool it to room temperature to obtain M 23 Ultrafine ternary eutectic high carbon chromium-molybdenum steel composed of C6 / M6C / Matrix.